Trade structure of Oman: evidence from gravity model - Hamid, Zarinah; Ma, Qinfen (College of Banking and Financial Studies, 2019)
This chapter attempts to determine the factors that affect trade by investigating the international trade structure of Oman with her five major trading partners namely China, USA, Singapore, Japan and Korea. It employs scaled and unscaled gravity model on a series of bilateral trade flows using time series and panel estimations during the period of 1981 and 2015. The findings from the empirical results of Oman with its trading partners have some implications. Increases in Oman’s economic size (positive coefficients of GDP) and Free Treatment Agreements (GAFTA) will increase the import, export and total trade. Common border and common language are likely to lower costs and boost international trade. Distance has a significant and negative effect on Oman’s import, export and total trade. Hence, Oman’s government should increase the infrastructure of transportation to increase trade flow. As the coefficient of Oman’s CPI is significant and positive, depreciation value will increase Oman’s import, which indicates the price of import goods is inelastic. The depreciation of the currency decreases export due to the price of export goods being inelastic. The findings of this chapter provide useful information for the formulation of strategies which would enhance Oman’s economic diversification programme. It also serves additional information as to whether it needs to realign the existing policies in order to promote a more favorable environment and sustainable development in Oman.